Shrimp fishery by stake nets in Cochin barmouth area with special reference to Metapenaeus monoceros(Fabricius) - Nandakumar, G (Indian Journal of Fisheries, 2011)
Shrimp fishery by stake nets in Cochin barmouth area with special reference to Metapenaeus monoceros(Fabricius)